Analisis Lean Service Menggunakan DMAIC untuk Mengurangi Waste pada Pelayanan di SAMSAT Bone Bolango - Paramani, Muh Mahabbatullah; Junus, Stella; Rasyid, Abdul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
SAMSAT Bone Bolango is one of the places providing services to the community in processing Motor Vehicle Tax. There are still many weaknesses in government public services, one of which is that the service system time is approximately 20-30 minutes. This research aims to identify waste and increase the productivity of the PKB service process at SAMSAT Bone Bolango. Based on results of service process flow mapping using Process Activity Mapping and Value Stream Mapping is known in total lead time service time was 1317.23 seconds and there was 54.45% non-value added activity time with the largest percentage causing waste, namely delay. From the results of the proposed improvements, a total lead time amounting to 861.74 seconds and enhancement Process Cycle Efficiency from 45.30% to 64.73%, this indicates that there has been an increase in company productivity after implementation lean service.